The Bermuda Triangle - Rosenberg, Aaron (New York, NY : Rosen Pub. Group, 2002)
Traces the history of the Bermuda Triangle, surveying some of the disappearances in that area and some of the many theories surrounding it.
Includes bibliographical references (p. 45).
Keywords: Bermuda Triangle -- Juvenile literature; Bermuda Triangle